2016
DOI: 10.1371/journal.pone.0147408
|View full text |Cite
|
Sign up to set email alerts
|

Co- and Post-Treatment with Lysine Protects Primary Fish Enterocytes against Cu-Induced Oxidative Damage

Abstract: The aim of the work was primarily to explore the protective activity pathways of lysine against oxidative damage in fish in vivo and in enterocytes in vitro. First, grass carp were fed diets containing six graded levels of lysine (7.1–19.6 g kg-1 diet) for 56 days. Second, the enterocytes were treated with different concentrations of lysine (0–300 mg/L in media) prior to (pre-treatment), along with (co-treatment) or following (post-treatment) with 6 mg/L of Cu for 24 h. The results indicated that lysine improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…The dietary lysine requirement was estimated to be 47.27 g/kg of dietary protein for maximum of PWG. This value was similar to our previous research for on-grown grass carp, which was 47.30 g/kg of dietary protein ( Li et al., 2016a , Li et al., 2016b ). Additionally, previous studies have indicated that challenge with A. hydrophila could lead to histopathological change ( Abdelhamed et al., 2017 ) and skin haemorrhage and lesions in fish ( Wang et al., 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The dietary lysine requirement was estimated to be 47.27 g/kg of dietary protein for maximum of PWG. This value was similar to our previous research for on-grown grass carp, which was 47.30 g/kg of dietary protein ( Li et al., 2016a , Li et al., 2016b ). Additionally, previous studies have indicated that challenge with A. hydrophila could lead to histopathological change ( Abdelhamed et al., 2017 ) and skin haemorrhage and lesions in fish ( Wang et al., 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The MDA content is used as a biomarker to measure the level of oxidative damage ( Wang et al., 2010 ). Our previous study reported that lysine excess could increase the content of MDA levels in grass carp intestine ( Li et al., 2016a , Li et al., 2016b ). These results help to explain our findings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The improvement in semen quality parameters of L-lysine treated groups in terms of sperm total motility, progressive motility, progressive fast motility, average path velocity, straight linear velocity and curvilinear velocity was observed (table 3 and 4).The improvement in these aforementioned parameters may be attributed towards anti-oxidative property of lysine (Li et al, 2016)which ultimately results in decreased lipid per oxidation, lesser production of reactive oxygen species, increased glutathione peroxidase and catalase in L-lysine treated groups.…”
Section: Discussionmentioning
confidence: 83%